(untitled) (Annals of Medical Research, 2022)
Aim: Favipiravir, first used for novel influenza strains, is used today in coronavirus disease 2019 (COVID-19). While many studies have been reported in the literature on hydroxychloroquine’s (HQ) arrhythmogenic adverse effects, data on favipiravir are limited. The authors purposed to demonstrate that the arrhythmic effects of favipiravir are not negligible. Materials and Methods: The researchers conducted a retrospective observational study on 194 COVID-19 patients. The study population was classified into two groups based on the treatment regimen: favipiravir (n=101) and HQ (n=93). Pre/post-medication electrocardiograms were evaluated for arrhythmic events. Results: Twenty of 101 (19.8%) subjects in the favipiravir group and 13 of 93 (13.9%) subjects in the HQ group had arrhythmogenic events (p=0.42). The most frequent arrhythmic events in the favipiravir group were sinus bradycardia (13 of 20, 65%) and third-degree atrioventricular block (4 of 20, 20%). Corrected QT (QTc) prolongation was the most seen arrhythmogenic adverse effect (9 of 13, 69%) in the HQ group. The proportion of patients with prolonged QTc were higher in the HQ group than the favipiravir group (9 vs. 3, p=0.04). However, the difference between final and baseline QTc did not differ between the HQ and the favipiravir group (11 [IQR:-9—57] vs. 12 [IQR:-7—103], p=0.59, respectively). The change between pre and post-treatment heart rate was more remarkable in the favipiravir group than the HQ group (12 [IQR:-6—70] vs. 5 [IQR:-8—41], p<0.001, respectively). Conclusions: Favipiravir was significantly associated with sinus bradycardia requiring drug withdrawal. Clinicians should more routinely implement arrhythmia monitoring for patients receiving favipiravir.